The influence of academic vocabulary knowledge on school performance. (June 2017) - Schuth, Elisabeth; Köhne, Judith; Weinert, Sabine
Abstract: While academic language is often assumed to impact children's school success, evidence for this claim is still limited. One reason is the lack of empirically sound test measures for academic language that are based on clear conceptualizations. In a study with 173 German fourth graders we investigated whether academic vocabulary knowledge predicts children's performance in school beyond general vocabulary knowledge, employing newly developed tasks to assess academic vocabulary. Analyses reveal that academic vocabulary rather than general vocabulary predicts grades in four subjects, controlling for age, gender, language background, and nonverbal cognitive abilities. These results support the claim that already in primary school academic language proficiency significantly influences academic careers. Highlights: Academic vocabulary knowledge significantly predicted four grades in primary school. Age, gender, language background, and non-verbal cognitive abilities were controlled. General vocabulary skills had no significant influence in the full model anymore. Academic vocabulary exerted the strongest effect on the grade in social studies. Results could help promoting these skills early in children's academic careers.